AB0580 Selological responce of the H1N1PDM influenza vaccine in patients with rheumatoid arthritis treated with monoclonal antibody therapy or conventional DMARDS, comparison with healthy adult. (23rd January 2014) - Tsuru, T.; Suzaki, M.; Maeda, K.; Nakashima, H.; Eto, T.; Ishibashi, M.; Manabe, J.; Terao, K.; Irie, S.
Abstract : Objectives: We investigated the immunogenicity of the vaccine for H1N1pdm influenza, which became a global pandemic in 2009/2010. We reported the vaccination study outcomes based on the patients with rheumatoid arthritis, however we would like to know how much serological response who are exposed to H1N1 pdm, are expected in patients with rheumatoid arthritis under monoclonal antibody therapy, conventional DMARDs compared to healthy adults. Methods: One hundred twenty-six patients (29 males and 97 females) with rheumatoid arthritis (RA) and thirty healthy volunteer were enrolled. In RA patients, conventional DMARDs, infliximab(INF), etanercept(ETA) and tocilizumab(TCZ) were treated by 59 patients, 27 patients, 18 patients, and 22 patients, respectively. Patients were vaccinated twice in September and October with the H1N1pdm influenza vaccine (Biken). Serum samples were taken prior to vaccination the first (S0) and second (S1) vaccinations, and in the fourth week after the second vaccination (S2), and serum antibody titres were measured using the haemagglutination inhibition (HI) assay. Using these data, we investigated the response rate (increase in HI titre ≥4-fold), seroprotection rate (HI titre ≥1:40), and seroconversion rate (increase in HI titre from pre-vaccination titre <1:10 to post-vaccination HI titre ≥1:40, or a 4-fold increase in post-vaccination titre from a pre-vaccination HI titre ≥1:10). Results: 1) The response rate at S1/S0 and S2/S0 are 59% and 69% in healthy volunteer, 60% and 74% in pts received DMARDs, 30% and 56% in pts received INF, 53% and 65% in pts treated ETA, and 77% and 76% in pts with TCZ. 2) Seroprotection rate at S1 and S2 are 34% and 45% in healthy volunteer, 40% and 47% in pts received DMARDs, 22% and 37% in pts received INF, 35% and 47% in pts treated ETA, and 50% and 48% in pts with TCZ. 3) Seroconversion rate at S1 and S2 are 55% and 66% in healthy volunteer, 59% and 68% in pts received DMARDs, 37% and 48% in pts received INF, 53% and 65% in pts treated ETA, and 64% and 71% in pts with TCZ. Conclusions: In this research on the pandemic influenza vaccine, we found no inhibition of immunogenicity in patients receiving tocilizumab compared to healthy volunteer and patients with monoclonal antibody or DMARDs. Disclosure of Interest: T. Tsuru Consultant for: USB, Employee of: Medical Co.LTA, M. Suzaki Employee of: Medical Co.LTA, K. Maeda: None Declared, H. Nakashima: None Declared, T. Eto Employee of: Medical Co.LTA, M. Ishibashi Employee of: Medical Co.LTA, J. Manabe Employee of: Medical Co.LTA, K. Terao Employee of: ChugaiPharmaceutical Co., LTD., S. Irie Employee of: Medical Co.LTA